Empowerment on Chinese Police Force's Role in Social Service - Wang, Xiaohai. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This is the first scholarly book to explore the empowerment and the social service role of frontline police officers in the People’s Republic of China. It approaches the study of role strain and empowerment, informed by local empirical data and personal experience. Thematically organized and focusing on those issues of greatest concern to the public, such as the dual social control (informal and formal) mechanism, mass line policing, strike-hard campaigns, police professionalization and professional ethics, as well as the paramilitary-bureaucratic structure in the Chinese police organization, it provides a detailed discussion of these and other contemporary issues. The book offers a valuable resource for students and researchers in the area of comparative policing and comparative criminal justice, as well as police professionals and policy-makers.